Intertrochanteric Fracture After Hip Resurfacing Arthroplasty Managed with a Reconstruction Nail - Jason Chow; Peter Kilby; Richard Freihaut (Journal of Orthopaedics, Trauma and Rehabilitation, 2013)
Periprosthetic fractures after hip resurfacings are rare occurrences that can pose a challenge to orthopaedic surgeons. With hip resurfacings becoming more common, the prevalence of these fractures is likely to increase because these patients are usually younger and more active. We report a case of traumatic periprosthetic proximal femur fracture treated with a reconstruction intramedullary nail technique.